Concise enantioselective synthesis of (2S,3S)-3-hydroxypipecolic acid via proline catalyzed alpha-aminooxylation of aldehydes and Pd-catalyzed ether directed aza-Claisen rearrangements - Ahuja, Brij Bhushan; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
An efficient approach to (2S,3S)-3-hydroxypipecolic acid with an overall yield of 10.2% and 98% ee starting from 1,5-pentanediol has been developed. The key steps employed in the synthesis are the D-proline catalyzed sequential alpha-aminooxylation/Horner-Wadsworth-Emmons olefination of an aldehyde and the Pd-catalyzed MOM-ether directed aza-Claisen rearrangement of an allylic trichloroacetimidate. (C) 2014 Elsevier Ltd. All rights reserved.